PERLINDUNGAN HUKUM KONSUMEN TERHADAP KERUSAKAN BARANG YANG DILAKUKAN OLEH JASA KURIR DARI PT. PAXEL ALGORITA UNGGUL - Daniella Sara Tiorida, (2022)
Expedition itself means a person who provides or services for the transportation and delivery of goods and has responsibility for the delivery of goods and the receipt of goods. Goods are sent using means of transportation using land routes such as cars, trucks, motorcycles, sea lanes such as ships and air routes such as airplanes. The existence of expeditions makes it easier to deliver goods with the help of third parties to carry out expedition activities. Third parties are called shipping companies where there is an agreement from the company as a seller and service users as consumers. To avoid mistakes or violations between sellers and consumers, in Indonesia, Article 8 of the 1999 Law on Consumer Protection was created to help overcome disputes experienced by consumers against actions by business actors where business actors have their own rights and obligations that must be carried out. This journal raises the case from PT. Paxel who was negligent in carrying out his duties in delivering goods where the goods were not delivered on time and arrived in the hands of consumers with damaged goods so that they were not given compensation that should have been given. It is, PT. Paxel violated Article 19 paragraph (2) of the Consumer Protection Act which is subject to administrative sanctions which must pay compensation wherein compensation is adjusted to the mutual agreement decided in court with the result of the court by mediation.